Motivasi Petani Untuk Bergabung Dalam Kelompok Tani di Desa Pagaran Tapah Kecamatan Pagarantapah Darussalam Kabupaten Rokan Hulu - Agung Yus Effin; Roza Yulida; Arifudin ' (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2014)
This research aims to determine intrinsic and extrinsic motivation of farmers to join farmer’s groups in Pagaran Tapah Village Pagaran Subdistrict of Tapah Darussalam District of Rokan Hulu. 62 independent smallholder farmers, who are members of farmer groups, were interviewed as respondents. They were choosen by disproposional random sampling. Data were analyzed by descriptive method, using a Summated Likert Scala Rating (SLR). The result showed that: (1) Intrinsic motivation of farmers is high, it can be seen from the score at enough category (3.29) and extrinsic motivation of farmers is also high, it can be seen from the socre at high category (3.40). Keywords: Motivation, motivation of  intrinsic, motivation of ekstrinsic, and group farmer